Analysis of nitrogen source assimilation in industrial strains of Aspergillus oryzae - Miki, Shouhei; Sakai, Kanae; Nakagawa, Takuro; Tanaka, Takumi; Liu, Liyun; Yamashita, Hideyuki; Kusumoto, Ken-Ichi (Journal of bioscience and bioengineering, 2024)
Nitrogen source assimilation is important for the biological functions of fungi, and its pathway has been deeply studied. Aspergillus oryzae mutants defective in nitrogen source assimilation are known to grow poorly on Czapek-Dox (CD) medium. In this study, we found an industrial strain of A. oryzae that grew very poorly on a CD medium containing sodium nitrate as a nitrogen source. We used media with various nitrogen components to examine the steps affecting the nitrogen source assimilation pathway of this strain. The strain grew well on the CD medium supplied with nitrite salt or ammonium salt, suggesting that the strain was defective in nitrate assimilation step. To ascertain the gene causing the defect of nitrate assimilation, a gene expression vector harboring either niaD or crnA of A. oryzae RIB40 was introduced into the industrial strain. The industrial strain containing the crnA vector recovered its growth. This is the first report that a mutation of crnA causes poor growth on CD medium in an industrial strain of A. oryzae, and crnA can be used as a transformation marker for crnA deficient strains. •An nitrate assimilation mutant was firstly found in industrial Aspergillus oryzae strains.•A vector harboring either wild type niaD or crnA was constructed and introduced.•The industrial strain containing the crnA vector recovered its growth.•Several industrial strains were found to possess the same sequence as mutated crnA.